The parotid tumours-benign and malignant: our experience - Patel, Nikhil D.; Mehta, Shivani M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Salivary gland tumors are uncommon and constitute a highly heterogeneous histopathological group of neoplasms. The present study aims to determine the correlation between the cytological and histopathological findings of parotid gland tumors, and preservation of the facial and posterior branch of the greater auricular nerve during parotid surgery. A study of 21 cases of parotid gland tumors was conducted at our hospital- GMERS Medical College and Civil Hospital, Valsad. All of them were clinically diagnosed and investigated. Hospital records of these patients including operative findings were analyzed concerning age, sex, indications for surgical management, and outcome. A total of 21 salivary gland tumors were diagnosed over 2 years representing pleomorphic adenoma was most commonly occurring in 15 (71%) cases followed by Warthin`s in 3 (14%) cases, mucoepidermoid carcinoma 2 (10%) and benign cystic lesion in 1 (5%) cases. Most of the parotid gland tumors occurred in the 20-60 years age group. Females were more commonly affected than males. The data discussed in this study was consistent with other hospital-based studies concerning age, sex, site, clinical presentation, diagnosis, complications, management, and outcome of these different types of parotid gland tumors.